Investigating the relationship between asthma symptoms and severity with television watching, computer use, and internet access among 13-14-year-old children in Yazd, Iran - Nasrin Behniafard; Zahra Nafei; Foad Forghani; Masoud Faisal; Mehran Karimi; Marzie Vaghefi (BMC, 2024)
Abstract Background Asthma is a prevalent chronic respiratory disease that affects individuals from childhood to adulthood. This study aimed to investigate the association between symptoms and severity of asthma with television viewing, computer and Internet use in adolescents, considering the lifestyle changes in recent decades. Methods This study was conducted in early 2020 as part of the Global Asthma Network 2020 survey, among 13-14-year-olds in Yazd, Iran. Participants were classified into case and control groups based on the presence and severity of asthma symptoms. The data was collected and analyzed using SPSS-20 software to compare the participants based on their screen time. Results The analysis of data collected from a total of 5141 students produced noteworthy results. A significant correlation was identified between the occurrence of wheezing in the past year, the presence of severe asthma, and the amount of time spent watching television, using a computer, or internet. The unadjusted model revealed that screen time of more than three hours, pet ownership, current smoking, and ever smoking were all significant predictors of wheezing and severe asthma. Smoking was the strongest predictor of asthma and its severity. After adjusting for confounding factors, the multiple logistic regression model confirmed that screen time of more than three hours remained a significant predictor of both asthma and its severity. Conclusion This study finds a significant association between media usage and asthma symptoms and severity. However, this association is influenced by lifestyle factors such as physical activity, obesity, diet, and exposure to indoor allergens. Further research is needed to better understand the complex interplay between media usage and asthma, considering the impact of these factors.